Technology and luxury hospitality AI, blockchain and the metaverse - Thaichon, Park; Dutta, Pushan Kumar 1985-; Chelliah, Pethuru Raj ca. 20./21. Jahrhundert; Gupta, Sachin (Routledge, 2024)
"The integration of pioneering information and communication technologies has transformed the hospitality sector. This ground-breaking book delves into the transformative power of cutting-edge technologies in the world of high-end travel and accommodation. As the digital revolution continues to reshape our lives, this book offers an exclusive look at how the hospitality industry is adapting and evolving to cater to the sophisticated tastes of the modern, tech-savvy traveller. In this eye-opening exploration, readers will be taken on a journey through the latest innovations in artificial intelligence, blockchain, and the metaverse, as they intersect with the world of luxury hospitality. From AI-driven concierge services and smart hotel rooms that cater to guests' every whim, to the democratization of luxury experiences through blockchain-based loyalty programs and the rise of virtual reality travel, this book reveals the extraordinary possibilities that lie ahead for the discerning traveller. With insights from international experts this edited collection provides a comprehensive and engaging overview of the current and future trends shaping the industry and will be valuable to scholars and postgraduate researchers across the hospitality sector, innovation and luxury management"--
Includes bibliographical references and index
2405
Keywords: Gastgewerbe / (DE-627)091361850 / (DE-2867)13307-2; Luxusgüter / (DE-627)091375932 / (DE-2867)10302-6; Digitalisierung / (DE-627)1028324774 / (DE-2867)30171-4; Künstliche Intelligenz / (DE-627)091373379 / (DE-2867)15611-3; Metaversum / (DE-627)1866176110 / (DE-2867)30381-0; Blockchain / (DE-627)1682222225 / (DE-2867)30190-0; Internet der Dinge / (DE-627)665021127 / (DE-2867)30072-6; Indien / (DE-627)091366895 / (DE-2867)17602-1; Welt / (DE-627)09140004X / (DE-2867)16809-5; Hospitality industry / Data processing; Hospitality industry / Information technology; Artificial intelligence; Blockchains (Databases); Metaverse